Moderasi Beragama Perspektif Buya Syafii Maarif dan Lukman Hakim Saifuddin: Sebuah Kajian Komparatif, Konseptual, Dan Implementatif - Supriyadi Ahmad (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
Religious moderation is a kind of discourse that relatively new and has been proposed by the Indonesian Ministry of Religion since 2019. Various reactions have emerged from the public, including pros and cons. The comparative thoughts of two national figures from Muhammadiyah and Nahdlatul Ulama, Syafii Maarif and Lukman Saifuddin regarding the concept and implementation of religious moderation described in this article. The research method used is library research, taken from the main works of the two figures as primary data, while secondary data taken from various written works by scholars in the form of books, magazines, freelance writing on social media, and alike. The conclusions of this study are as follows: The concept of religious moderation proposed by Syafii Maarif is religion as the basis for the revival of the nation, Indonesian Islam, democratic Islam, and modern Islam. Meanwhile, the religious moderation offered by Lukman Saifuddin is an attitude and view that is not excessive, not extreme, and not radical (tatharruf). This has been carried out as an endeavor and dynamic process to build perspectives, attitudes and religious practices in a fair way and balanced manner. The aim of religious moderation raised by Syafii Maarif is the forming of a society that is peaceful, harmonious, tolerant and upholds a sense of unity between nations and countries.Keywords : Religious Moderation,  Syafii Maarif, Lukman Hakim Saifuddin, Comparative, Conceptual,  and Implementative AbstrakModerasi beragama merupakan diskursus yang relatif baru yang diwacanakan oleh Kementerian Agama RI sejak tahun 2019. Berbagai reaksi muncul dari masyarakat antara yang pro dan yang kontra. Artikel ini membandingkan pemikiran dua tokoh nasional dari Muhammadiyah dan Nahdlatul Ulama, yaitu   Ahmad Syafii Maarif dan Lukman Hakim Saifuddin tentang konsep dan implementasi moderasi beragama. Metode penelitian ini adalah penelitian kepustakaan (library reseach)  dengan data primer diambil dari karya utama kedua tokoh tersebut, dan data sekunder diambil dari berbagai karya tulis para cendekiawan baik yang berbentuk buku, majalah, tulisan lepas di media sosial, atau yang sejenis. Kesimpulan dari penelitian ini adalah Konsep moderasi beragama yang dimajukan oleh  Syafii Maarif adalah agama sebagai landasan kebangkitan bangsa, Islam keIndonesiaan, Islam demokratis,  dan Islam modernitas. Sedangkan moderasi beragama yang ditawarkan oleh Lukman Hakim Saifuddin adalah sikap dan pandangan yang tidak berlebihan, tidak ekstrem, dan tidak radikal (tatharruf). Hal ini dilakukan sebagai  ikhtiar dan proses dinamis dari upaya membangun cara pandang, sikap, dan praktik beragama dalam kehidupan bersama secara adil dan seimbang. Tujuan modersi beragama yang dimunculkan oleh Buya Ahmad Syafii Maarif dengan terciptanya masyarakat yang damai, harmonis, toleran,  dan menjunjung tinggi rasa kesatuan antar bangsa dan negara.Kata Kunci: Moderasi Beragama, Buya Ahmad Syafii Maarif, Lukman Hakim Saifuddin, Komparatif, Konseptual, dan Implementatif